Between raisins, “fructas” and fondant: labels information and memories (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This paper aims to analyze Brazilian chocolate labels (1937-1945) by understanding them as informational and heritage documents that articulate textual, imagistic and symbolic representations. Using an interdisciplinary approach, it investigates how these artifacts communicate technical, symbolic and affective knowledge through textual, visual and terminological representations. This qualitative research applied methods of content and iconographic analysis to labels collected in private collections. Based on the Communicative Theory of Terminology, Representations of Information and Imagery and Documentary Diplomacy, it highlights the importance of these materials for digital collections and the need for preservation policies, revealing labels as devices of social Memory and identity.
Keywords: food ephemera; information representation; social memory; terminology; Brazilian chocolate